Digestibility of dried distiller’s grains with solubles in steam-flaked or dry-rolled corn diets - May, M.L.; Hands, M.J.; Quinn, M.J.; Wallace, J.O.; Murray, Leigh W.; Reinhardt, Christopher D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In previous experiments, we observed that the nutritional value of dried distiller’s grains is less when added to finishing diets made of steam-flaked corn than when added to diets of dry-rolled corn. We hypothesized that effects of grain processing on value of distiller’s grains are attributable to differences in the digestion characteristics of grains processed via flaking or dry rolling. In this study, our objective was to evaluate differences in ruminal metabolism and total tract digestion of diets made from dry-rolled or steam-flaked corn with and without dried distiller’s grains.
Keywords: Beef; Cattle; Dry-rolling; Steam-flaked